Kirurška obravnava bolnikov z vstavljenimi srčnimi spodbujevalniki in vsadnimi defibrilatorji - Šervicl-Kuchler, Darja (Zdravniški vestnik, 2009)
Background The number of patients with implanted pacemakers (PM) and implantable cardioverter/defibrillators (ICD) is constantly increasing. If these patients need surgery, we have to adapt the procedures during the surgery to prevent complications. The pacemaker may be disturbed by individualsources of electromagnetic field (EMI). This can present as asynchronous pacing, inhibition, stimulation on the upper limit, ventricular fibrillation, burns in the endocardium and pacemaker damage. Implantable cardioverter/defibrillator can be switched off or it can deliver countershocksunder the influence of EMI. Recommendations The cardiologist or cardiovascular surgeon must check these patients a short time prior to surgery. During the surgery a bipolar electrocauter or ultrasonic scalpel should be used. The use of a unipolar electrocauter is not recommended for surgery above the waist. If the surgeon uses it anyway, there are some directions that have to be followed, and are described in this article. The function R (R is responsible for physiological rate adapation) of the pacemaker and the implanted cardioverter defibrillator have to be switched offjust prior to surgery. In the operating room, an external defibrillator, external pacemaker, a programming device and a magnet should always be present. The patient also has to be checked after the surgery, because failureof the device may not be apparent for up to 48 hours after surgery. Conclusions Pacemakers and cardioverter/defibrillators may be disturbed by individual sources of electromagnetic field. If we consider all the recommendations, the surgery will be much safer for this cohort of patients.
Keywords: Cardiac Pacing, Artificial; defibrilatorji; Defibrilatorji, vsadek; Defibrillators, Implantable; elektromagnetno polje; Intraoperative Period; kirurško zdravljenje; Medoperativno obdobje; Pooperativne komplikacije; Postoperative Complications; Predoperativna oskrba; Preoperative Care; srčni spodbujevalci; Srčno vzpodbujanje, umetno; zapleti